Influence of some soil factors and organic amendments on Pseudomonas fluorescens and sheath blight of rice - A.P. SINHA, RAJBIR SINGH* and (Indian Phytopathology, 2009)
Influence of soil pH, zinc and organic amendments on Pseudomonas fluorescens and sheath blight of rice in nursery and under glasshouse conditions were evaluated. Incidence of sheath blight was higher (45.01%) in acidic soil (5.2) as compared to neutral soil i.e.7.0 (40.42%) or alkaline soils i.e. pH 8.3 (37.43%). Effectiveness of Pfr 1 on sheath blight was higher in neutral soil than in acidic or alkaline soil. Soil application of Pfr 1 in zinc amended soil or with out zinc application showed 15.96% and 20.36% disease severity, respectively. Soil without zinc and bioagent applications resulted in 45.63% sheath blight severity. Soil incorporation of neem cake enhanced the effectivity of the bioagent in increasing seedling emergence (66.60%) and reducing sheath blight severity (65.89%) and disease incidence (77.15%), as compared to the control. Application of farm yard manure + Pfr 1 or dhiancha (Sesbania eculeata) + Pfr 1 in soil resulted in 59.25% and 57.51% reduction in disease severity.